Moocs-Based Solar System Module for Class VII Junior High School Students - Okta Rahma Putri; Eko Risdianto; Indra Sakti (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2024)
This research aims to develop a digital module based on MOOCs on solar system material for class VII junior high school students. This research is a Research and Development study (R&D) with a 3D model which includes the Define, Design and Development stages. The data collection techniques used were observation, interviews and questionnaires. The instruments used in this research were observation sheets, teacher interview guide sheets, expert validation sheets, and student response test sheets. Data analysis techniques are carried out qualitatively and quantitatively. The research results show that digital modules based on MOOCs are valid and can be used. The test results of students' responses to the digital modules developed showed a very good category. The conclusion from the results of this research shows that the digital module developed was declared feasible by the expert team and received a positive response from students to be continued in wide-scale trials to see the product's effectiveness.